PERANAN RUKUN WARGA DALAM UPAYA ADAPTASI MASYARAKAT TERHADAP PERUBAHAN IKLIM : Studi Deskriptif di Kampung Inspirasi RW 17 Desa Jatiendah Kecamatan Cilengkrang Kab Bandung - Ihsanuddin, - (2018)
Ketika lingkungan menjadi tidak ramah dan mengancam kehidupan manusia. Kegiatan-kegiatan yang dilakukan manusia di era modern tidak diimbangi dengan kesadaran lingkungan, yang akhirnyanya menyebabkan permasalahan lingkungan. Permasalahan lingkungan saat ini yang menjadi perhatian pemerintah adalah pemanasan global. Pemanasan global merupakan isu lingkungan hidup yang dapat menyebabkan perubahan iklim. Perubahan iklim memiliki dampak besar bagi kehidupan manusia. Hal itu pun dirasakan oleh sejumlah warga yang bermukim di wilayah RW 17 desa Jatiendah kecamatan Cilengkrang kabupaten Bandung. Selama beberapa tahun terakhir warga merasakan perubahan lingkungan yang cukup signifikan, seperti curah hujan yang terus meningkat, bencana banjir, serta kerentanan terhadap wabah penyakit. Penelitian ini bertujuan untuk mengkaji peranan Rukun Warga dalam upaya adaptasi masyarakat terhadap perubahan iklim. Metode yang digunakan dalam penelitian ini adalah observasi dan wawancara mendalam. Hasil dari penelitian ini menunjukkan Bentuk komunikasi yang dilkukan oleh pengurus RW 17 desa Jatiendah yaitu dengan cara komunikasi satu arah dimana berbicara secara langsung kepada masyarakat di kantor RW. Kegiatan yang dilakukan oleh warga sesuai dengan program kerja yang dibuat oleh pengurus Rukun Warga 17. Masyarakat pun merasakan dampak besar dari program Rukun Warga yakni dari segi lingkungan, sosial dan ekonomi. Keyword : adaptasi masyarakat, peranan, perubahan iklim, rukun warga -------- When the environment becomes friendly and threaten human life, and therefore requires awareness together to overcome it. The threat can be broadly categorized as the impact of climate change. It was also felt by some residents who settled in the RW 17 Jatiendah village subdistricts Cilengkrang Bandung regency. Over the last few years residents feel the significant environmental changes, such as increasing rainfall, floods, and susceptibility to disease outbreaks. Under such circumstances, the board of Rukun Warga 17 Jatiendah Village perform various actions related to the initiation of adaptation in order to adapt to the impacts of climate change so that these vulnerabilities were able minimized. During the 5 years of the RW board continue to dock these efforts through programs based on saving the environment, until final in 2015 RW 17 Jatiendah Village crowned as the "Inspiration Village" by the Director Ministry of Environment and Forestry (KLHK) This research is aims to examine more deeply about the form type of communication adopted by the Chairman of RW 17 Jatiendah Village, identify the kinds of activities by residents as a form of adaptation to climate change, and outlines the impact felt by the citizens of these activities related to economic, social, and the environment. The object of this research is the board of RW 17 and some of Jatiendah's peoples. The method used in these is observations and depth interviews, for further descriptive analysis. The results of this study indicate that this form of communication made by the board of RW 17 which is 2-way communication with citizens is intense and with the attitude of the intervention and the firmness of the board of RW 17 against its citizens related to the programs organized by the pengurust, thus all of the work program relating to climate change adaptation efforts are considered successful in terms of economic, social, and environment capable of sustaining the welfare of residents of RW 17 Jatiendah's peoples. Residents also felt the positive impact on the implementation of the program, including the people's economy into a stable, rising spirit of mutual cooperation and ownership of citizens. Keyword : The role, neighborhoods, community adaptation to climate change